Reflexology in oncological treatment - a systematic review - Moritz Klaus; Sabine Kutschan; Heidrun Männle; Jutta Hübner; Jennifer Dörfler (BMC, 2024)
Abstract Background As cancer and its therapy comes with a wide range of negative effects, people look for options to mitigate these effects. Reflexology is among the options of complementary medicine. Method In March 2022 a systematic search was conducted searching five electronic databases (Embase, Cochrane, PsychInfo, CINAHL and Medline) to find studies concerning the use, effectiveness and potential harm of reflexology on cancer patients. Results From all 821 search results, 29 publications concerning 26 studies with 2465 patients were included in this systematic review. The patients treated with reflexology were mainly diagnosed with breast, lung, gastrointestinal and hematological cancer. Outcomes were mainly pain, quality of life, anxiety, depression, fatigue. The studies had moderate to low quality and reported heterogeneous results: Some studies reported significant improvements in above mentioned outcomes while other studies did not find any changes concerning these endpoints. Conclusion Due to the very heterogeneous results and methodical limitations of the included studies, a clear statement regarding the effectiveness of reflexology on cancer patients is not possible. The current evidence indicates that reflexology is superior to passive control groups for pain, quality of life and fatigue, however, more studies with comparable active control groups are needed.